Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Pada Perusahaan Sektor Teknologi Yang Terdaftar Di Bei Tahun 2021 Sampai 2023 - Rabani, Imelivia Cahya; Husadha, Cahyadi; Kurniawan, Dody (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
In Indonesia, technology has developed rapidly and has become an important part of people's lives. Over the past six years, especially during the pandemic between 2020 and 2022, information and communication technology (ICT) has experienced positive growth. Although the technology sector has received considerable attention, the movement of company shares in this sector shows fluctuations that can certainly affect investors' perceptions of company value. This study aims to analyze the influence of Net Profit Margin (NPM), Current Ratio (CR), and Debt To Equity Ratio (DER) on company value in the technology sector listed on the Indonesia Stock Exchange during the period 2021–2023. This study uses a quantitative approach with secondary data and purposive sampling in sample selection. Data analysis was conducted using EViews 12 software, through several stages, including descriptive statistical tests, selection of panel data regression models, classical assumption tests, t-tests, F-tests, and determination coefficients. The analysis results indicate that Net Profit Margin (NPM) and Current Ratio (CR) do not significantly influence company value. Meanwhile, the Debt-to-Equity Ratio (DER) has a significant partial effect on company value. Simultaneously, the three financial performance indicators—NPM, CR, and DER—have a significant effect on company value. This finding suggests that capital structure, represented by DER, is an important aspect in assessing the value of technology sector companies.